2012
DOI: 10.1073/pnas.1110120109
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold protein Disc large homolog 1 is required for T-cell receptor-induced activation of regulatory T-cell function

Abstract: + CD25 high regulatory T cell (Treg) suppression of inflammation depends on T-cell receptor-mediated Nuclear Factor of Activated T cells c1 (NFATc1) activation with reduced Akt activity. We investigated the role of the scaffold protein Disc large homolog 1 (Dlgh1) in linking the T-cell receptor to this unique signaling outcome. The Treg immunological synapse (IS) recruited fourfold more Dlgh1 than conventional CD4 + T-cell IS. Tregs isolated from patients with active rheumatoid arthritis, or treated with tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 50 publications
5
60
1
Order By: Relevance
“…The SQSTM1-Lck-Dlgh1-K v 1.3 signaling axis may be important in regulation of T cell activation, since K v 1.3, Dlgh1, and Lck translocate to the IS together with TCRs during activation of T cells, leading to cytokine production and proliferation of human CD4 + T cells [113]. Analysis of Dlgh1 gene-targeted mice shows that peripheral lymph node Dlgh1 -/-T cells exhibited enhanced proliferative response to TCR-induced stimulation, while thymic development was normal [114].…”
Section: Roles Of Sqstm1 In Th2 Cell Differentiation and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQSTM1-Lck-Dlgh1-K v 1.3 signaling axis may be important in regulation of T cell activation, since K v 1.3, Dlgh1, and Lck translocate to the IS together with TCRs during activation of T cells, leading to cytokine production and proliferation of human CD4 + T cells [113]. Analysis of Dlgh1 gene-targeted mice shows that peripheral lymph node Dlgh1 -/-T cells exhibited enhanced proliferative response to TCR-induced stimulation, while thymic development was normal [114].…”
Section: Roles Of Sqstm1 In Th2 Cell Differentiation and Activationmentioning
confidence: 99%
“…Since Lck is important in GATA-3 expression [110], we suggest a possible cooperation of SQSTM1 and Lck in GATA-3 expression and following cytokine secretion. In T lymphocytes, Lck links between K v 1.3 and CD4 on T cell activation [113]. CD4 interacts with other immune T cell receptors during activation [113].…”
Section: Role Of β1-integrin In Vascular Cells and T Cellsmentioning
confidence: 99%
“…We and others have demonstrated that Dlg1 plays a vital role in T cell development, activation and effector responses utilizing Dlg1 knockdown and overexpression systems (4,5,7,9,10,16). However, initial knockout studies that ablate Dlg1 early in T cell development do not show striking functional differences, likely because of compensation from other Dlg1 family members (36,37).…”
Section: T Cellsmentioning
confidence: 99%
“…We and others have demonstrated that Dlg1 specifies TCR signal transduction, by coordinating the activation of p38 through the alternative pathway (5,7,16). The alternative p38 pathway is initiated downstream of the TCR, and requires the activity of proximal tyrosine kinase Lck and Zap70 (17).…”
Section: P Roper Activation Of Cd8mentioning
confidence: 99%
See 1 more Smart Citation